SOCIAL CHANGE IN MENSERE VILLAGE TEBAS DISTRICT SAMBAS REGENCY - Zuri Astari (ADISAM Publisher, 2024)
Every individual has unlimited interests, interests that influence aspects of social life can result in social change in society. Humans think and are able to work to do something that ultimately brings change to the surrounding environment. One of the causes of social change is the desire to adapt to the environment in order to become advanced and not miss out on the latest issues. This research aims to find out how social changes have occurred in Mensere Village, Tebas District, Sambas Regency. This research uses a qualitative approach with descriptive research type. The results of the research show that there are changes that have occurred in Mensere Village, Tebas District, Sambas Regency. This is proven by several social changes that have occurred. First, changes in norms in society. Second, people's lifestyles directly or indirectly follow foreign cultural lifestyles due to the influence of social media. Third, population changes are increasing every year, which if life's needs cannot be met, it will have a negative impact on the economy, education, ecology and others. Fourth, there is a change in buying and selling transactions that people currently carry out, namely online transactions via social media